Teaching Strategies in Portuguese as an Additional Language - Perna, Cristina Becker Lopes; Molsing, Karina Veronica; Sarmento, Simone; Ramos, Yadhurany dos Santos (BELT - Brazilian English Language Teaching Journal, 2016)
.